Correction of murine mucopolysaccharidosis VII by a human beta-glucuronidase transgene. - Kyle, J W (1990)
We recently described a murine model for mucopolysaccharidosis VII in mice that have an inherited deficiency of beta-glucuronidase (beta-D-glucuronoside glucuronosohydrolase, EC 3.2.1.31). Affected mice, of genotype gusmps/gusmps, present clinical manifestations similar to those of humans with mucopolysaccharidosis VII (Sly syndrome) and are shown here to have secondary elevations of other lysosomal enzymes. The mucopolysaccharidosis VII phenotype in both species includes dwarfism, skeletal deformities, and premature death. Lysosome storage is visualized within enlarge vesicles and correlates biochemically with accumulation of undegraded and partially degraded glycosaminoglycans. In this report we describe the consequences of introducing the human beta-glucuronidase gene, GUSB, into gusmps/gusmps mice that produce virtually no murine beta-glucuronidase. Transgenic mice homozygous for the mucopolysaccharidosis VII mutation expressed high levels of human beta-glucuronidase activity in all tissues examined and were phenotypically normal. Biochemically, both the intralysosomal storage of glycosaminoglycans and the secondary elevation of other acid hydrolases were corrected. These findings demonstrate that the GUSB transgene is expressed in gusmps/gusmps mice and that human beta-glucuronidase corrects the murine mucopolysaccharidosis storage disease.